2002
DOI: 10.1021/ac011028b
|View full text |Cite
|
Sign up to set email alerts
|

Micromachined Nanocalorimetric Sensor for Ultra-Low-Volume Cell-Based Assays

Abstract: Current strategies for cell-based screening generally focus on the development of highly specific assays, which require an understanding of the nature of the signaling molecules and cellular pathways involved. In contrast, changes in temperature of cells provides a measure of altered cellular metabolism that is not stimulus specific and hence could have widespread applications in cell-based screening of receptor agonists and antagonists, as well as in the assessment of toxicity of new lead compounds. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 29 publications
3
49
0
Order By: Relevance
“…Since biomolecules are often resolved in liquid, there is serious evaporation problem without careful chamber system during the temperature scanning process [38]. Hence the simple open type structure which is utilized by most MEMS isothermal titration calorimeters cannot be applied to the MEMS DSC [39,40].…”
Section: Thermal Insulation Systemmentioning
confidence: 99%
“…Since biomolecules are often resolved in liquid, there is serious evaporation problem without careful chamber system during the temperature scanning process [38]. Hence the simple open type structure which is utilized by most MEMS isothermal titration calorimeters cannot be applied to the MEMS DSC [39,40].…”
Section: Thermal Insulation Systemmentioning
confidence: 99%
“…The relatively large size of these sensors limits the functional complexity of the pill for a given size of capsule. Adapting existing semiconductor fabrication technologies to sensor development [12][13][14][15][16][17] has enabled the development of highly functional units for data collection, whilst the exploitation of integrated circuitry for sensor control, signal conditioning and wireless transmission [18] has extended the concept of single channel radiotelemetry to remote distributed sensing from microelectronic pills.…”
Section: International Context Of the Workmentioning
confidence: 99%
“…In open-chamber nanocalorimeters, the sample is dispensed directly into a microwell that is placed on the sensor chip [17], [24]- [27]. For instance, Johannessen et al demonstrated the feasibility of monitoring heat production by a very small number of mammalian cells [17], [28] in sample volumes of hundreds of pl.…”
Section: Introductionmentioning
confidence: 99%